Recurrent compartment syndrome in a patient with clinical features of a connective tissue disorder1. Issue 6 (30th April 2013) - Barajas, Brenda D.; Sun, Angela; Rimoin, David L.; Reinstein, Eyal
Abstract Arterial complications are common in vascular type Ehlers–Danlos syndrome (EDS), accounting for 66% of first complications. Several cases in the literature have documented acute compartment syndrome (ACS) following vascular rupture in vascular type EDS. Other disorders of connective tissue have also demonstrated vascular fragility, leading to arterial aneurysm and rupture, but there have been no documented cases of ACS. Here, we report on a female patient with a history of recurrent compartment syndrome who exhibits some clinical findings seen in hypermobile and vascular EDS; however she does not meet clinical and molecular diagnostic criteria for either of them. We further review the literature on ACS in heritable connective tissue disorders and suggest that compartment syndrome may rarely complicate other heritable disorders of connective tissue. © 2013 Wiley Periodicals, Inc.